2011
DOI: 10.1111/j.1469-0691.2011.03514.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in patients with bloodstream infections caused by KPC-producing Klebsiella pneumoniae and impact of appropriate antimicrobial treatment

Abstract: Bloodstream infections (BSIs) caused by Klebsiella pneumoniae carbapenemases (KPC)-producing K. pneumoniae (KPC-KP) are associated with high mortality rates. We investigated outcomes, risk factors for mortality and impact of appropriate antimicrobial treatment in patients with BSIs caused by molecularly confirmed KPC-KP. All consecutive patients with KPC-KP BSIs between May 2008 and May 2010 were included in the study and followed-up until their discharge or death. Potential risk factors for infection mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
333
12
21

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(401 citation statements)
references
References 24 publications
35
333
12
21
Order By: Relevance
“…46 Poor outcomes are also due to treatment with ineffective, empiric antibiotics before carbapenem resistance is identified by the laboratory. 47,48 In one study of neutropenic patients with CRE bloodstream infections, nearly 90% of patients were started on ineffective therapy at presentation and a median of 55 hours elapsed between time of culture collection and administration of effective antibiotic therapy. 45 Because mortality from sepsis increases 7.6% for every hour's delay in effective antibiotic administration, 49 diagnostics that speed up detection and appropriate treatment of CRE by even a few hours should improve outcomes of patients with invasive CRE infections.…”
Section: Treatment Implications Of Rapid Detection Of Crementioning
confidence: 99%
See 1 more Smart Citation
“…46 Poor outcomes are also due to treatment with ineffective, empiric antibiotics before carbapenem resistance is identified by the laboratory. 47,48 In one study of neutropenic patients with CRE bloodstream infections, nearly 90% of patients were started on ineffective therapy at presentation and a median of 55 hours elapsed between time of culture collection and administration of effective antibiotic therapy. 45 Because mortality from sepsis increases 7.6% for every hour's delay in effective antibiotic administration, 49 diagnostics that speed up detection and appropriate treatment of CRE by even a few hours should improve outcomes of patients with invasive CRE infections.…”
Section: Treatment Implications Of Rapid Detection Of Crementioning
confidence: 99%
“…48,[52][53][54] This remains controversial as not all studies found a survival advantage among patients with CRE infections who received combination therapy vs. monotherapy and results of ongoing randomized studies are not yet available. 55 There is some evidence that non-colistin based regimens had worse outcomes than colistin-based regimens.…”
Section: Treatment Implications Of Rapid Detection Of Crementioning
confidence: 99%
“…The most common carbapenemases in K. pneumoniae are the K. pneumoniae carbapenemases (KPC) [6]. KPC-associated infections are predominantly nosocomial, involving patients with multiple risk factors, and the mortality rates can be high [7].…”
Section: Introductionmentioning
confidence: 99%
“…[89][90] For the treatment of BSIs sustained by KPC-producing Enterobacteriacae, which are the most common carbapenem-resistant nosocomial isolate, combination regimens including at least 2 active drugs have been associated with improved clinical outcomes and reduced mortality in comparison with the use of only one active drug, in particular when the combination includes a carbapenem. 45,[91][92] Tumbarello et al analyzed a cohort of 125 patients with KPC-K. pneumoniae-BSIs and reported a significantly lower 30-day mortality in patients receiving a combination regimen compared with the ones treated with a monotherapy (34,1% vs 54,3%, P D 0,02). In particular, multivariate analysis found that a targeted therapy with meropenem in combination with colistin and tigecycline was independently associated with reduced mortality (OR:0.11; 95%CI: .02-.69; P D 0.01).…”
Section: Gram Negative Bacteriamentioning
confidence: 99%